Taxonomic review of dinoflagellate cyst species mentioned by Regali, Uesugui & Santos (1974) - Arai, Mitsuru [UNESP]; Premaor, Eduardo; Lana, Cecília Cunha; Ferreira, Elizabete Pedrão (Sociedade Brasileira de Paleontologia, 2024)
The publication entitled ‘Palynology of Mesozoic and Cenozoic strata from Brazil’ by Regali, Uesugui & Santos provided a palynostratigraphic framework that has been utilized extensively in the petroleum industry and in academic research. Accordingly, it is considered as a classic paper on Brazilian Mesozoic–Cenozoic palynostratigraphy. Many of the miospore species (spores and pollen grains) proposed by those authors – e.g., Alaticolpites limai, Aquilapollenites magnus, Cicatricosisporites cristatus, Echitriletes muelleri, Psilastephanocolporites variabilis, Psilastephanoporites brasiliensis, Retitricolpites amapaensis, Retitriletes sommeri, Sergipea naviformis, S. variverrucata, Steevesipollenites alatiformis, S. giganteus, S. nativensis, and Tricornites elongatus – continue to be recognized as valid names by the international palynological community. Nevertheless, some of the dinoflagellates are subject to taxonomic revision. Critical re-examinations have been conducted by newer (post-1980) generations of palynologists. The present work is intended as an update concerning the taxonomic validity of fossil dinocysts. This review is a debt that Brazilian palynologists owe to the international palynological community. Because of the lack of adequate updated review, even important compilations, such as the ‘Lentin and Williams Index of Fossil Dinoflagellates’, have published misjudged identifications of Regali et al.’s species. Taxonomic descriptions of two species formalized here – Glaphyrocysta espiritosantensis and Exochosphaeridium bahiaensis – are presented in English in Appendix A, to meet the requirement of the International Code of Nomenclature (ICBN).
REVISÃO TAXONÔMICA DAS ESPÉCIES DE CISTOS DE DINOFLAGELADOS MENCIONADAS POR REGALI, UESUGUI & SANTOS (1974)
Keywords: biostratigraphy; Brazil; Cenozoic; Cretaceous; dinoflagellates; palynology